A HUMANISTIC PHILOSOPHICAL CRITIQUE OF THE DEHUMANIZATION OF ELEMENTARY SCHOOL TEACHERS ROLES IN THE ERA OF ARTIFICIAL INTELLIGENCE - Khovifah Puspita Sari; Munir Munir; Ismail Sukardi (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
This study examines the phenomenon of the dehumanization of elementary school teachers’ roles in the era of Artificial Intelligence (AI) through the humanistic philosophical perspectives of Carl Rogers, Abraham Maslow, and Paulo Freire. Using a qualitative method based on library research and content analysis of various recent scholarly sources, the study shows that while the presence of AI in elementary education can provide efficiency, personalization, and administrative convenience, it also has the potential to weaken the quality of human relationships that form the fundamental foundation of elementary education. Forms of dehumanization in the context of elementary education can be observed in the reduction of empathetic interactions, the loss of personal touch in learning, the shift of pedagogical authority toward automated systems, and the increasing emphasis on quantitative metrics that neglect students’ emotional needs and self-actualization. From a humanistic perspective, this study emphasizes that elementary school teachers continue to play a crucial role as facilitators of authentic relationships, moral and emotional guides, and drivers of students’ critical consciousness. Therefore, the integration of AI in elementary education should be directed in a humanistic manner, ensuring that technology functions as a supportive tool to strengthen—rather than replace—the essence of humanization in modern education.